PENGEMBANGAN PROFIL DIGITAL DESA GAJAHREJO SEBAGAI BRANDING DESA WISATA - Izzalqurny, Tomy Rizky; Yanto, Alif Faruqi Febri; Sulistyorini, Anita; Ferdiansyah, Rifaldy Adinandra (Jurnal Abdi Insani, 2024)
Gajahrejo Village in Gedangan District, Malang Regency, has great tourism potential with six attractive beaches and coban. However, the challenges in promoting the tourism potential of this village are still significant, especially due to limited access to digital technology and internet infrastructure. The purpose of this community service is to develop tourism content in Gajahrejo Village, thus developing a digital profile as a branding strategy for tourist villages is expected to increase the visibility of Gajahrejo Village among domestic and international tourists. This community service was carried out in Gajahrejo Village, Gedangan, Malang Regency, from April to October 2024. The methods of this community service are developing digital content, training the community in managing social media, and creating an official village website and social media accounts. The results of this community service show a significant increase in digital interaction and tourist awareness of Gajahrejo Village. Through a sustainable digital-based branding strategy, Gajahrejo Village has the potential to become a leading tourist destination in Malang Regency.